A beam-tracking framework for THz networks - Stratidakis, Giorgos; Droulias, Sotiris; Alexiou, Angeliki (Frontiers in Communications and Networks, 2022)
Millimeter wave (mmWave) and terahertz (THz) frequencies are attractive for increased bandwidth applications, however are vulnerable to blockage and suffer from high pathloss. While the use of directional antennas can potentially mitigate these effects, the need for careful alignment becomes crucial, especially when the user moves. In this context, to ensure a reliable link, several parameters must be taken into account, such as the type of user's motion, the location of the access point (AP), the shape of the area, the beamwidth, etc. In this work, the link reliability is divided into two main categories, the trajectory tracking resolution and the angular resolution. To address the challenges of both categories, a beam-tracking algorithm that promises high tracking reliability and low pilot overhead is proposed. The algorithm employs multiple cooperating APs and a hierarchical codebook and the performance of the proposed tracking method is evaluated through Monte-Carlo simulations with the probability of success, the average number of pilots per timeslot and the mean square error (MSE) as metrics, for different tracking estimation frequencies and different number of blocked links.